1997
DOI: 10.1016/s0375-9601(97)00468-4
|View full text |Cite
|
Sign up to set email alerts
|

Homoclinic orbits and chaos in a second-harmonic generating optical cavity

Abstract: We present two large families ofŠilnikov-type homoclinic orbits in a two modemodel that describes second-harmonic generation in a passive optical cavity. These families of homoclinic orbits give rise to chaotic dynamics in the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Wersinger, Finn, and Ott [29] used a forced and damped version of the three-wave equations to study instability saturation by nonlinear mode coupling and found irregular solutions indicating the presence of a strange attractor. See also [1,12,13,24] for more detailed studies of the perturbed three-wave system.…”
Section: Equations Of Motionmentioning
confidence: 99%
“…Wersinger, Finn, and Ott [29] used a forced and damped version of the three-wave equations to study instability saturation by nonlinear mode coupling and found irregular solutions indicating the presence of a strange attractor. See also [1,12,13,24] for more detailed studies of the perturbed three-wave system.…”
Section: Equations Of Motionmentioning
confidence: 99%
“…We also found the relations of these results to the non-acceleration theorem [3], averaging [4,5], WKB 6 stability theory [6], and Lagrangian-mean fluid equations for prescribed wave displacements such as those of [7]. Poincm6 for dynamics on a Lie algebra, in that they depend on a parameter and this parameter in fluid dynamics applications has the interpretation of being advected, or Lie dragged, as with the density in compressible fluid flow.…”
Section: The Project's First Year --New Wave Mean-flow Interaction (mentioning
confidence: 99%